PETUALANGAN DALAM E-COMIC PADA KONTEN BILANGAN BULAT - Ismianda Rohadatul ‘Aisy; Shinta Wulandari; Alfian Mucti (Mathematics Education and Application Journal (META), 2025)
High school students in Tarakan also experienced errors in integer operations, even though they should have mastered this material at an earlier level. This problem is closely related to classroom learning practices, especially the use of learning media that should facilitate cognitive engagement and meaningful learning experiences. Given the need for media, students' status as digital natives, and a survey showing that 67.2% of students are interested in adventure-themed comics, it is necessary to develop e-comics on integer operations material with adventure themes. The 4-D model development research was used by modifying it to 3-D (define, design, and develop). The research subjects consisted of six Year 10 students selected through purposive sampling. Data collection used qualitative and quantitative data obtained through observation, interviews, questionnaires, and documentation. Data analysis was conducted descriptively using a Likert scale to assess expert validity and student responses, with media feasibility criteria deemed feasible if they achieved a minimum percentage of 61%. The validation results showed that the media met the feasibility criteria, with material and language expert assessments of 91.25% and media and language expert assessments of 90.79%, both of which were classified as highly feasible. Limited trials involving six students with diverse abilities showed positive responses with a feasibility percentage in the feasible category. Thus, e-comic media with an adventure theme are feasible for use as learning media for tenth-grade students. Keywords: Adventure Theme, E-comics, Integer Counting Operations, Learning Media.   Kesalahan dalam operasi bilangan bulat juga dialami siswa Sekolah Menengah Atas di Tarakan, padahal seharusnya materi tersebut telah dikuasai di jenjang sebelumnya. Permasalahan tersebut berkaitan erat dengan praktik pembelajaran di kelas, terutama dengan pemanfaatan media pembelajaran yang seharusnya dapat memfasilitasi keterlibatan kognitif dan pengalaman belajar bermakna. Penggabungan kebutuhan media, karakteristik siswa sebagai digital natives, dan hasil survey 67,2% siswa tertarik pada komik bertemakan petualangan. Sehingga diperlukan pengembangan media e-comic dengan tema petualangan pada materi operasi bilangan bulat. Penelitian pengembangan model 4-D digunakan dengan memodifikasi menjadi 3-D (define, design, dan develop). Subjek penelitian terdiri dari 6 siswa kelas X yang dipilih melalui teknik purposive sampling. Pengumpulan data menggunakan data kualitatif dan kuantitatif yang dilakukan melalui observasi, wawancara, angket, dan dokumentasi. Analisis data dilakukan secara deskriptif menggunakan skala Likert untuk menilai validitas ahli dan respon siswa, dengan kriteria kelayakan media yang dinyatakan layak apabila mencapai persentase minimal 61%. Hasil validasi menunjukkan bahwa media memenuhi kriteria kelayakan, dengan penilaian ahli materi dan bahasa sebesar 91,25% serta ahli media dan bahasa sebesar 90,79%, keduanya termasuk kategori sangat layak. Uji coba terbatas terhadap enam siswa dengan karakteristik kemampuan yang beragam menunjukkan respons positif dengan persentase kelayakan pada kategori layak. Sehingga, media e-comic dengan tema petualangan layak digunakan sebagai media pembelajaran bagi siswa kelas X. Kata kunci: E-comic, Media Pembelajaran, Operasi Hitung Bilangan Bulat, Tema Petualangan